2009
DOI: 10.1007/s00296-009-0973-9
|View full text |Cite
|
Sign up to set email alerts
|

A systematic medline analysis of therapeutic approaches in ankylosing spondylitis

Abstract: Ankylosing spondylitis (AS) is a chronic inflammatory disorder involving the sacroiliac joints (SIJs), spine and less frequently the peripheral joints. Traditionally, it is well recognised that AS is a challenging disease to manage due to the lack of effective therapeutic options. Current evidence would suggest this has changed and there are now a number of therapies available that provide persistent control of inflammatory symptoms with improvement in daily function. NSAIDs remain the first step in patient tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 85 publications
0
24
0
Order By: Relevance
“…Two RCTs failed to demonstrate the superiority of a combination of MTX with infliximab versus infliximab alone in the treatment of active AS over 1 year (category B evidence102 257 280). Regular treatment with infliximab was more effective than ‘on-demand’ treatment for treating AS (category A evidence 405 405a). …”
Section: Tnf Blocking Agents (Tnfi)mentioning
confidence: 99%
See 3 more Smart Citations
“…Two RCTs failed to demonstrate the superiority of a combination of MTX with infliximab versus infliximab alone in the treatment of active AS over 1 year (category B evidence102 257 280). Regular treatment with infliximab was more effective than ‘on-demand’ treatment for treating AS (category A evidence 405 405a). …”
Section: Tnf Blocking Agents (Tnfi)mentioning
confidence: 99%
“…In a head-to-head comparison trial of a conventional DMARD (sulfasalazine) with a TNFi (etanercept), the latter was more effective, including for heel enthesitis (category A evidence327 405 406). Enthesitis scores have also been shown to improve in studies with other TNFi.…”
Section: Tnf Blocking Agents (Tnfi)mentioning
confidence: 99%
See 2 more Smart Citations
“…A systematic analysis of this newer approach demonstrated that patients who are diagnosed early, often with a simple x-ray, and begin treatment with biologics early will have a slower progression of the disease (Goh & Samanta, 2009).…”
Section: Ankylosing Spondylitismentioning
confidence: 99%